PECULIARITIES OF WINTER WHEAT YIELD FORMATION IN ORGANIC PLANTS UNDER INSUFFICIENT MOISTENING - Marenych, M. M.; Diazhuk, R. U.; Ivaniuta, O. O.; Merezen, N. L. (Scientific Progress & Innovations, 2021)
The analysis of scientific publications shows that choosing varieties and fore-crops for wheat cultivation technology is one of the main and effective ways of wheat yield management in the conditions of organic production and enables to increase the yield by 7.5-26%. According to the scientific publications, choosing the varieties for cultivation and developing optimal crop rotations are considered to be the main methods of wheat yield increase. This aspect is also especially important for improving soil fertility, however rather often it does not provide agro-ecosystems with the sufficient amount of the most important element for plant nutrition – nitrogen. The variance ratio for ordinary plants and in the region on the average made 20.4 %. The yield capacity of organic plants varied considerably more – the variance ratio made 34.2 %. Such difference shows significantly larger dependence of organic agro-ecosystems on the conditions of cultivation years as compared with ordinary or intensive agro-ecosystems. It should also be mentioned that there is a strong direct correlation – r=0.84 between yield indicators, which testifies to the possibility of developing effective agronomic practices to stabilize organic grain production. The obtained results of wheat yield analysis in production organic plants show that the yield variability considerably exceeds this parameter in the plants cultivated according to intensive technologies. This fact proves the difficulties in the processes of productivity management of organic agro-ecosystems. The scientifically grounded choice of varieties for the cultivation and correct sequence in crop rotation are the main factors of the yield stability. The part of variety impact in organic agro-ecosystems reaches 88.2 %, and the impact of the preceding crop – up to 97 % depending on the year conditions. The analysis of multi-factor complex, in which the year of cultivation was included as a factor shows that agro-ecological conditions can make about 80% of yield variability on the whole. Pea, lentil, and cucurbits crops are the best fore-crops for the conditions of insufficient moistening. The lowest yields were obtained after esparcet and sunflower. The share of factor interaction amounts to 2.3-6.6 % and is statistically reliable. The highest yield levels in different years were obtained from Sotnytsia, Bohemia, Antara, and Epokha Odesla varieties. In 2021, Sahaidak, Vidrada, and Sotnytsia wheat varieties sown after pea, lentil, and cucurbits crops were grown. The analysis of variance did not reveal the considerable effect of preceding crop and variety properties because of their actual equivalence, which appeared in situations under the conditions of the separately taken year. The yield was within 3.09- 3.41 t/ha. The share of factor interaction makes 2.3-6.6% and is statistically reliable.